Design and Motion Analysis of a Planetary Gear Type Power Coupling Device Used in HEV - Gao Aiyun; Tian Songwen (Jixie chuandong)
Based on the power system parameters of a certain type Hybrid Electric Vehicle（ HEV）,a planetary gear type power coupling device is designed for power transmission structure which can meet the requirement of power. Then,the main parameters of the planetary gear set and the transmission ratio are determined. The planetary gear type power coupling device modeling,assembly and movement simulation are carried out by using the UG NX8. 0. Through analyzing the results of movement simulation and theoretical calculation,it is validated that the design of planetary gear type power coupling device is reasonable,and lay a foundation for the subsequent finite element analysis and structure optimization.